Characteristics and sociocultural impacts of small pelagic fishing by migrant fishers in Benin, West Africa - Ahouansou Montcho, S; SALAKO, Kolawolé Valère; CHADARE, FLORA JOSIANE; Gnansounou, Constant Sètondé; SOHOU, ZACHARIE; Failler, Pierre; Glèlè kakaï, Romain; ASSOGBADJO, ACHILLE EPHREM (My University, 2022)
Small pelagic fish species contribute substantially to the food security and livelihoods of local communities in developing countries. In West Africa, and particularly in Benin, small pelagic fisheries attract many migrant fishers who are key actors in the sector. This study assessed the characteristics and sociocultural impacts of the small pelagic fishery in Benin using qualitative approaches, including focus group discussions (n = 9), in-depth interviews (n = 35), a literature review, direct observations and secondary data. The findings showed that indigenous fishers from Benin and foreign fishers from Ghana are the two major groups of migrant fishers involved in small pelagic fishing in Benin. These fishers mostly use three categories of fishing gear: gillnets, seine nets, and hooks and lines. Over the period 2014–2018 the annual catch fluctuated between 1 123 and 2 040 tonnes, with the peak catch recorded in 2018, with a commercial value of €3 030 587. Apart from migrant fishers, fishmongers constitute another important pillar of the value chain. Conflicts among migrant fishers in the sector in Benin are related to landing fees and fishing gears. We discuss the urgent need to give attention to the sector through quantitative research and law enforcement to ensure its sustainability.
Keywords: coastal artisanal fishing; fishing gear; fishmongers; focus group discussions; Ghanaian fishers; small-scale fishing; value chain